2010
DOI: 10.1037/a0019165
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual distinctiveness supports detailed visual long-term memory for real-world objects.

Abstract: Humans have a massive capacity to store detailed information in visual long-term memory. The present studies explored the fidelity of these visual long-term memory representations and examined how conceptual and perceptual features of object categories support this capacity. Observers viewed 2,800 object images with a different number of exemplars presented from each category. At test, observers indicated which of 2 exemplars they had previously studied. Memory performance was high and remained quite high (82%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
492
12
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(554 citation statements)
references
References 109 publications
40
492
12
10
Order By: Relevance
“…Mean saturation and value, on the other hand, as well as the first three moments of the pixel intensity histogram, exhibited weaker correlations with memorability ( Figure 5). These findings concord with other work that has shown that perceptual features are not retained in long term visual memory [11]. In order to make useful predictions, more descriptive features are likely necessary.…”
Section: Color and Simple Image Featurescontrasting
confidence: 53%
See 2 more Smart Citations
“…Mean saturation and value, on the other hand, as well as the first three moments of the pixel intensity histogram, exhibited weaker correlations with memorability ( Figure 5). These findings concord with other work that has shown that perceptual features are not retained in long term visual memory [11]. In order to make useful predictions, more descriptive features are likely necessary.…”
Section: Color and Simple Image Featurescontrasting
confidence: 53%
“…This is not surprising given the large role that semantics play in picture memory [13,11]. To investigate the role of object semantics, we performed the same regression as above, except this time using the entire joint (object class, statistic) distributions as features.…”
Section: Object and Scene Semanticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli consisted of indoor and outdoor scene images derived from two image sets (Goh et al, 2004;Konkle et al, 2010). The images were first screened to remove any legible writing (to preclude this as a strategy to remember particular images) as well as people (since these were particularly salient relative to other scene content).…”
Section: Methodsmentioning
confidence: 99%
“…Twelve participants rated the perceptual similarity of items within each pair from 1 (highly similar) to 5 (highly distinctive), and 11 rated intra-pair conceptual similarity on the same scale. Participants were asked to base perceptual similarity judgements on visual features such as shape or colour, and to base conceptual similarity judgements on how well the images corresponded to the same kind of object, i.e., two mountain bikes would be judged as conceptually similar, whereas a collie and bulldog, although both belonging to the basic-level category 'dog' should be rated less conceptually similar (Konkle et al, 2010). Image pairs were presented until 800 ms after a response was made, up to a maximum presentation time of 6000 ms.…”
Section: Similarity Ratingsmentioning
confidence: 99%